Increased Lysine Content Is the Main Characteristic of the Soluble Form of the Polyamide Cyanophycin Synthesized by Recombinant Escherichia coli - Frommeyer, Maja (American Society for Microbiology, 2013)
Cyanophycin, a polyamide of cyanobacterial or noncyanobacterial origin consisting of aspartate, arginine, and lysine, was synthesized in different recombinant strains of Escherichia coli expressing cphA from Synechocystis sp. strain PCC 6308 or PCC 6803, Anabaena sp. strain PCC 7120, or Acinetobacter calcoaceticus ADP1. The molar aspartate/arginine/lysine ratio of the water-soluble form isolated from a recombinant strain expressing CphA(6308) was 1:0.5:0.5, with a lysine content higher than any ever described before. The water-insoluble form consisted instead of mainly aspartate and arginine residues and had a lower proportion of lysine, amounting to a maximum of only 5 mol%. It could be confirmed that the synthesis of soluble cyanobacterial granule polypeptide (CGP) is independent of the origin of cphA. Soluble CGP isolated from all recombinant strains contained a least 17 mol% lysine. The total CGP portion of cell dry matter synthesized by CphA(6308) from recombinant E. coli was about 30% (wt/wt), including 23% (wt/wt) soluble CGP, by using terrific broth complex medium for cultivation at 30°C for 72 h. Enhanced production of soluble CGP instead of its insoluble form is interesting for further application and makes recombinant E. coli more attractive as a suitable source for the production of polyaspartic acid or dipeptides. In addition, a new low-cost, time-saving, effective, and common isolation procedure for mainly soluble CGP, suitable for large-scale application, was established in this study.